Proceedings of the Graduate Research in Education (GREDuc) 2015 Seminar - Faculty of Educational Studies (Faculty of Educational Studies, 2015)
The Graduate Research in Education (GREDuc) 2015 Seminar, held on December 20, 2015, and organized by the Faculty of Educational Studies, Universiti Putra Malaysia, focused on the theme Diversity in Research.